Routine vs no episiotomy in primigravida: a pilot RCT on perineal injury and pelvic floor dysfunction - Kumari, Archana; Deoghare, Manasi; Kumari, Rajesh; Vatsa, Richa; Sharma, Alpana; Sharma, K. Aparna; Sagar, Komal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: The present study compared the effect of ‘routine-episiotomy’ vs ‘no-episiotomy’ on perineal injury and pelvic floor function during normal vaginal delivery in primigravida. Methods: This open-label RCT allocated women in the second stage of labour to routine mediolateral episiotomy or no-episiotomy (1:1) using concealed computer-generated randomisation. Episiotomy was avoided in the no-episiotomy group unless instrumental delivery was required for maternal or foetal reasons. Perineal trauma, suturing characteristics, pain, pelvic-floor function, urinary and anal incontinence were assessed at 24 hours, 36 hours, and 3 months postpartum. Pre and post-episiotomy biomarkers assessed the tissue-level injury. Analyses were conducted in STATA with significance at p<0.05. Results: Out of 125 women screened initially, n=42 were randomised to episiotomy and no-episiotomy groups, while n=83 were excluded due to caesarean section or instrumental delivery. The episiotomy group had a shorter second stage of labour (p=0.034) and longer tears (p=0.047). More women in the no-episiotomy group used analgesics within 24 hours (p=0.048), but none after 36 hours. There was no significant difference in perineal pain, subjective tear grading, or pelvic-floor dysfunction, anal and urinary incontinence in both groups. Furthermore, biomarkers showed a significant increase in MDA (p=0.005) in the no-episiotomy group and increased TNF-α (p=0.042) in the episiotomy group, while CK and IL-6 changes were not significant. Conclusions: Considering no additional clinical benefits of episiotomy compared to no-episiotomy in terms of perineal pain, pelvic-floor dysfunction, or most biomarkers, routine episiotomy should be discouraged in clinical practice.